Stress of algicidal substances from a bacterium Exiguobacterium sp. h10 on Microcystis aeruginosa. (28th November 2016) - Li, Y.; Liu, L.; Xu, Y.; Li, P.; Zhang, K.; Jiang, X.; Zheng, T.; Wang, H.
Abstract: Microcystis aeruginosa is a cyanobacterial bloom‐causing species and is considered a serious threat to human health and biological safety. In this study, the algicidal bacterium h10 showed high algicidal effects on M. aeruginosa 7820, and strain h10 was confirmed to belong to the genus Exiguobacterium, for which the name Exiguobacterium sp. h10 is proposed. Algicidal activity and mode analysis revealed that the supernatant, rather than the bacterial cells, was responsible for the algicidal activity, indicating that the algicidal mode of strain h10 is by indirect attack through the production of algicidal substances. Analysis of the algicidal substance characteristics showed a molecular weight of <1000 Da and that algicidal substances exhibit high thermal stability and pH instability, and the characteristic functional groups of the algicidal substance mainly included carbonyl, amino and hydroxyl groups. Under the effects of the algicidal substance, the cellular pigment content was significantly decreased, and the algal cell structure and morphology were seriously damaged. The results indicate that the algicidal bacterium Exiguobacterium sp. h10 could be a potential bio‐agent for controlling cyanobacterial blooms of M. aeruginosa . Significance and Impact of the Study: In this study, the effects of algicidal substances from an algicidal bacterium Exiguobacterium sp. h10 on the toxic cyanobacterium, Microcystis aeruginosa 7820, were first investigated. The algicidal mode of action was confirmed as an indirect attack through the production of algicidal substances. The characteristics of the algicidal substance were determined, especially the functional groups analysis that confirmed the algicidal substances were glycolipid mixtures. With the stress of algicidal substances, the algal chlorophyll a synthesis, cell structure and morphology were seriously damaged. This study proved that algicidal bacteria are promising sources of potential cyanobacterial bloom‐control, and provided good procedures for the identification and analysis of an algicidal bacterium and substances. Abstract : Significance and Impact of the Study: In this study, the effects of algicidal substances from an algicidal bacterium Exiguobacterium sp. h10 on the toxic cyanobacterium, Microcystis aeruginosa 7820, were first investigated. The algicidal mode of action was confirmed as an indirect attack through the production of algicidal substances. The characteristics of the algicidal substance were determined, especially the functional groups analysis that confirmed the algicidal substances were glycolipid mixtures. With the stress of algicidal substances, the algal chlorophyll a synthesis, cell structure and morphology were seriously damaged. This study proved that algicidal bacteria are promising sources of potential cyanobacterial bloom‐control, and provided good procedures for the identification and analysis of an algicidal bacterium and substances.